Plastic Litter as Pollutant in the Aquatic Environment: A mini-review - Rifka Rimbi Anggraini; Yenny Risjani; Uun Yanuhar (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightThe issue of plastic litter and microplastics which is currently of special concern in global particularly IndonesiaThe review of size, colour and shape of microplastics that becomes part of the plastic litterThe observed review highlight of plastic litter and microplastics impact on environmental health particularly aquatic biotaAbstractThe negative impact that comes from plastic litter in the aquatic environment is a scourge for the entire world including Indonesia.Plastic litter has a huge influence on the most biota who lives in symbiosis with along the aquatic environment as it is able to sustainability. Moreover, there are other factors that cause the death of aquatic biota. Nowadays, the negative impact of plastic litter occurs on an ongoing basis through the food chain process which until now has not been well studied. Therefore, it is necessary to do further studies on the influence of the food chain as a vector of plastic litter distribution, particularly microplastic on aquatic biota from the first trophic level to high trophic levels.